The Role of Gamification and Interactive Learning in Deep Learning for EFL Students - Rizkyka Febrianisa; Abdul Halim; Dzul Rachman (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2025)
This study examines the impact of gamification and interactive learning on students’ achievement and engagement in English as a Foreign Language (EFL), alongside their perceptions of the learning environment. Employing a quasi-experimental posttest-only control group design, 60 eleventh-grade students at MAN 1 Samarinda were randomly assigned to an experimental group (gamification via Baamboozle) or a control group (conventional instruction). Data collection instruments included engagement observations, achievement tests, and Likert-scale perception questionnaires. Statistical analyses comprised normality and homogeneity tests, independent t-tests, and N-Gain calculations using SPSS. Results indicate that the experimental group significantly outperformed the control group (posttest means: 91.00 vs. 85.33, p=0.005) and exhibited higher engagement levels. Positive student perceptions were reported regarding motivation, teacher-student interaction, and learning atmosphere, though vocabulary development requires further focus. The integration of gamified elements with interactive learning promotes effective, meaningful, and engaging educational experiences. Continued application and adaptation of gamification strategies are recommended, with future research advised to explore long-term effects on communication skills.